2005
DOI: 10.1063/1.1996834
|View full text |Cite
|
Sign up to set email alerts
|

Double-pulse machining as a technique for the enhancement of material removal rates in laser machining of metals

Abstract: Several nanosecond 0.53-μm laser pulses separated by several tens of nanoseconds have been shown to significantly enhance (three to ten times) material removal rates while minimizing redeposition and heat-affected zones. Economic, high-quality, high-aspect ratio holes (>10:1) in metals are produced as a result. A phenomenological model whereby the second laser pulse interacts with the ejecta produced by the first laser pulse and in close proximity to the material surface is consistent with the observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(58 citation statements)
references
References 11 publications
1
55
0
2
Order By: Relevance
“…The specification on the hole, which is necessary for D-T fuel filling as well, are severe, with a diameter of 5-µm maximum through most of the 160-µm wall. This is accomplished with a Nd-YAG laser, wavelength equal to 532 nm, 4-ns laser pulses using a double pulse technique (Forsman et al, 2005). A radiographic image of a typical laser drilled hole through a 167.1-µm Be capsule wall is shown in Figure 3.…”
Section: Figurementioning
confidence: 99%
“…The specification on the hole, which is necessary for D-T fuel filling as well, are severe, with a diameter of 5-µm maximum through most of the 160-µm wall. This is accomplished with a Nd-YAG laser, wavelength equal to 532 nm, 4-ns laser pulses using a double pulse technique (Forsman et al, 2005). A radiographic image of a typical laser drilled hole through a 167.1-µm Be capsule wall is shown in Figure 3.…”
Section: Figurementioning
confidence: 99%
“…Molten material is often observed long after pulse termination, demonstrated in the case of nanosecond pulses [30,31] and involves the interplay of several phenomena including hydrodynamic instabilities and vapour-assisted ejection. Surface vapour pressure as well as supra-surface ejecta detonations have also been attributed to melt ejection via pressure gradients across the irradiated zone [13,34]. The specific mechanisms responsible for material ejection depend on the geometry and rate of energy deposition.…”
Section: Phenomenological Backgroundmentioning
confidence: 99%
“…Doublepulse delivery profiles in the nanosecond regime have been proposed and investigated by Forsman [13] and Wang [14] demonstrating enhanced material removal rates by tuning the delivery time of the secondary pulse. The increased penetration depth was phenomenologically attributed to a secondary, reverse travelling blast wave; a consequence of the heated cloud of ejecta vaporising [13]. Similar results were reported by Liu et al [15] and more recently by Veiko et.…”
Section: Introductionmentioning
confidence: 99%
“…Nanosecond laser pulses separated by several tens of nanoseconds are shown that they can enhance the material removal rates while minimizing the heat-affected zone [16]. Experiments on the ultrashort dual-pulse laser drilling of copper using different wavelengths (800 nm and 532 nm) have also been investigated [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous experiments on the enhancement of metal drilling using a dual-pulse nanosecond laser have been presented [15][16][17]. Nanosecond laser pulses separated by several tens of nanoseconds are shown that they can enhance the material removal rates while minimizing the heat-affected zone [16].…”
Section: Introductionmentioning
confidence: 99%